Cytokine Profile in Patients Undergoing Minimally Invasive Surgery with Balanced Anesthesia - Orosz, Jose Eduardo B. [UNESP]; Braz, Mariana Gobbo [UNESP]; Golim, Marjorie de Assis [UNESP]; Barreira, Marcio Antonio A. [UNESP]; Fecchio, Denise [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, José Reinaldo Cerqueira [UNESP] (Springer/plenum Publishers, 2012)
Patients undergoing surgical procedure develop an inflammatory response due to surgical trauma that may be modulated by anesthetics. The aim of this study was to investigate the cytokine profile in the plasma of adult patients who underwent minimally invasive surgery with balanced anesthesia with propofol, fentanyl, and sevoflurane. The study included 15 healthy patients scheduled for tympanoplasty or septoplasty under balanced anesthesia. Blood samples were drawn at four time points: before anesthesia, before surgery, 120 min after anesthesia induction, and on the first postoperative day. Plasma interleukin (IL)-1 beta, -2, -4, -6, -8, -10, -12, TNF-alpha, and INF-gamma levels were assessed by flow cytometry. IL-6 levels were elevated on the day after the surgery (p < 0.001). All other cytokines did not change either during or after balanced anesthesia (p > 0.05). In conclusion, balanced anesthesia with propofol, fentanyl, and sevoflurane anesthesia is not associated with intraoperative changes in the plasma cytokines in healthy patients undergoing minimally invasive otorhinological surgeries. Considering IL-6 results, a postoperative inflammatory response may have occurred due to surgical stress.
Keywords: balanced anesthesia; sevoflurane; minor surgical procedures; cytokines; flow cytometry